Piéron's law and optimal behavior in perceptual decision-making - Van Maanen, Leendert; Grasman, Raoul P.; Forstmann, Birte U.; Wagenmakers, Eric-Jan (Frontiers in Neuroscience, 2012)
Piéron's Law describes a psychophysical regularity between mean response times and stimulus intensity in signal detection tasks. In this paper we extend this notion to perceptual two-choice decision-making, and demonstrate that Piéron's Law holds as the discriminability between two competing choices is manipulated. We present a Bayesian ideal observer model that explains why a Piéron-like regularity is found when stimulus discriminability is manipulated, and discuss how this model can be extended to cover signal detection tasks.